2023
DOI: 10.1038/s41598-023-40948-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-differential association of suicide attempts with thyroid dysfunction in first-episode and drug-naïve young major depressive disorder patients with comorbid anxiety

Gang Ye,
Ying Yuan,
Zhe Li
et al.

Abstract: This study aimed to explore sex differences in the relationship between thyroid function indicators and suicide attempts in first-episode and drug-naïve young major depressive disorder (MDD) patients with comorbid anxiety (MDA). A total of 917 MDD patients (aged 18–35 years) were recruited. The Hamilton depression rating scale (HAMD-17), Hamilton anxiety rating scale (HAMA), positive and negative syndrome scale (PANSS) positive subscale and clinical global impression of severity scale (CGI-S) were used. 467 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Earlier studies have found that females attempt suicide significantly more often than males, while completed suicides occur more frequently among males (Miranda-Mendizabal et al, 2019). In our previous study, we identified sex differences in the relationship between thyroid function markers and suicide attempts among young patients with MDD combined with anxiety (Ye et al, 2023).…”
Section: Introductionmentioning
confidence: 66%
“…Earlier studies have found that females attempt suicide significantly more often than males, while completed suicides occur more frequently among males (Miranda-Mendizabal et al, 2019). In our previous study, we identified sex differences in the relationship between thyroid function markers and suicide attempts among young patients with MDD combined with anxiety (Ye et al, 2023).…”
Section: Introductionmentioning
confidence: 66%